2012
DOI: 10.1016/j.renene.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Domestic application of micro wind turbines in Ireland: Investigation of their economic viability

Abstract: a b s t r a c tElectricity generation from renewable sources of energy will be a key part in the development of future strategies for many countries globally. This renewable electricity generation will be hugely important for Ireland, due to its lack of fossil fuel resources. The extremely good wind resource available provides Ireland with the opportunity of generating vast amount of electricity from wind energy. Large-scale wind electricity generation reached 1264 MW installed capacity by January 2010 in Irel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Additionally, another remarkable feature of wind energy is its wide accessibility in many areas of the world. Globally, renewable energy resources are abundantly available, and wind in particular is easy to harness in different regions (Li et al 2012;O'Rourke et al 2009). The statistics have shown that the wind power potential in the world is higher than our present demands of electricity consumption Abstract The knowledge of the probabilistic wind speed distribution is of particular significance in reliable evaluation of the wind energy potential and effective adoption of site specific wind turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, another remarkable feature of wind energy is its wide accessibility in many areas of the world. Globally, renewable energy resources are abundantly available, and wind in particular is easy to harness in different regions (Li et al 2012;O'Rourke et al 2009). The statistics have shown that the wind power potential in the world is higher than our present demands of electricity consumption Abstract The knowledge of the probabilistic wind speed distribution is of particular significance in reliable evaluation of the wind energy potential and effective adoption of site specific wind turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the model used to describe their performance should also differ. A typical model for a wind turbine is described below [18][19][20]: (29) where Pe,ave is the average output power of the wind generator at wind speed V (m/s), Per is the nominal power (kW), uc is the startup rotating speed (m/s), ur is the nominal speed (m/s), uf is the final rotating speed (m/s), and c and k are the coefficients of correlation.…”
Section: Basic Mathematical Model Of Wind Generatormentioning
confidence: 99%
“…Thus, fossil fuels are still used even if not by electrical heaters. Renewable energy is encouraged by governments and societies, therefore the use of renewable sources such as solar, geothermal and wind energy [2], [3], [4] to produce electricity offers great opportunity for reducing the fossil fuels consumption level.…”
Section: Introductionmentioning
confidence: 99%